Hematopoietic Stem Cell–Derived Cancer–Associated Fibroblasts Are Novel Contributors to the Pro-Tumorigenic Microenvironment()() - McDonald, Lindsay T. (Neoplasia, 2015)
Targeting the tumor microenvironment is critical toward improving the effectiveness of cancer therapeutics. Cancer-associated fibroblasts (CAFs) are one of the most abundant cell types of the tumor microenvironment, playing an important role in tumor progression. Multiple origins for CAFs have been proposed including resident fibroblasts, adipocytes, and bone marrow. Our laboratory previously identified a novel hematopoietic stem cell (HSC) origin for CAFs; however, the functional roles of HSC-derived CAFs (HSC-CAFs) in tumor progression have not yet been examined. To test the hypothesis that HSC-CAFs promote tumor progression through contribution to extracellular matrix (ECM) and paracrine production of pro-angiogenic factors, we developed a method to isolate HSC-CAFs. HSC-CAFs were profiled on the basis of their expression of hematopoietic and fibroblastic markers in two murine tumor models. Profiling revealed production of factors associated with ECM deposition and remodeling. Functional in vivo studies showed that co-injection of HSC-CAFs with tumor cells resulted in increased tumor growth rate and significantly larger tumors than tumor cells alone. Immunohistochemical studies revealed increased blood vessel density with co-injection, demonstrating a role for HSC-CAFs in tumor vascularization. Mechanistic in vitro studies indicated that HSC-CAFs play a role in producing vascular endothelial growth factor A and transforming growth factor–β1 in endothelial tube formation and patterning. In vitro and in vivo findings suggest that HSC-CAFs are a critical component of the tumor microenvironment and suggest that targeting the novel HSC-CAF may be a promising therapeutic strategy.